Indigeneity and decolonization in the Bolivian Andes : ritual practice and activism - Burman, Anders, 1977- (Lexington Books, 2017)
This book explores how Evo Morales's victory in the 2005 Bolivian presidential elections led to Indigeneity as the core of decolonization politics. Burman analyzes how Indigenous Aymara ritual specialists are essential in representing this Indigeneity in official state ceremony and in legitimizing the president's role as "the Indigenous president."